ПРИСКОРЕННЯ ДІЇ АВТОМАТИЧНОГО ЧАСТОТНОГО РОЗВАНТАЖЕННЯ ЕНЕРГОСИСТЕМИ ЗА РАХУНОК ВИКОРИСТАННЯ ІНФОРМАЦІЇ ПРО ШВИДКІСТЬ ЗНИЖЕННЯ ЧАСТОТИ - Авраменко, В.М.; Юнєєва, Н.Т.; Гурєєва, Т.М. (Інститут електродинаміки НАН України, Київ, 2016)
It is proved that the use of devices which measure the decrease of the frequency ensures the requirements of the emergency of frequency oscillations. Setting reasonable terms of automation, which uses a similar device. According to the results of the analysis "Ukrenergo" has developed a new version of the document "The use of emergency control system to prevent and eliminate or reduce the dangerous frequency increase in power systems", which address the issues of practical implementation of the AFU-S. The effectiveness of AFU-S demonstrated by the emergency department of the Kiev region of UPS of Ukraine. References 4, figure 1.